Acetylated histone variant H2A.Z is involved in the activation of neo-enhancers in prostate cancer - Fátima Valdés-Mora (Nature Portfolio, 2017)
Acetylation of the histone variant H2A.Z at gene promoters is associated with oncogene activation; however, it is unclear if such modification has a role in regulating the function of enhancers. Here the authors show that acetylated H2A.Z is redistributed at cancer neo-enhancers and regulates the activity of specific enhancers of cancer-related genes.